Covid-19 vs. BCG Universal Immunization: Statistical Significance in the Early Phase of the Pandemics - Serge Dolgikh (Ital Publication, 2021)
A possible correlation between the impact of Covid-19 and universal immunization program against tuberculosis with Bacillus Calmette-Guérin (BCG) vaccine was suggested previously, based on apparent correlation between lower impact of the epidemics and a record of national BCG immunization program. In this work a time-adjusted dataset of Covid-19 statistical data by national and subnational health jurisdictions at the time point of six months after the local arrival of the epidemics was used to perform a statistical analysis of the significance of the correlation hypothesis between universal BCG immunization and a milder early phase Covid-19 scenario. With the data accumulated up to the point of the analysis, the significance of the correlation hypothesis was evaluated both qualitatively and quantitatively with the conclusion that it has achieved statistically significant level of confidence. The conclusions of this research can be used in development of epidemiological policy as well as the rationale to investigate the origin and mechanisms of a broad immunity protection that can be associated with an early-age exposure to BCG vaccine.   Doi: 10.28991/SciMedJ-2021-03-SI-8 Full Text: PDF